Dakwah di Media Digital Sebuah Analisis Representasi Nilai-Nilai Islam Pada Film Merindu Cahaya De Amstel: Da'wah in Digital Media: An Analysis of the Representation of Islamic Values ​​in the Film Merindu Cahaya De Amstel - Hamandia, Muhammad Randicha; Hertimi, Sri; Umariani, Afriyanti (Yayasan Sagita Akademia Maju, 2025)
Film is one of the most effective media for preaching in conveying moral and religious messages, including in the context of Islamic preaching. In this case, film acts as a means of communication that can reach a wider audience. One interesting example is the film